Uma, nove ou dez narrativas sobre as licenciaturas em ciências e matemática em Mato Grosso do Sul - Mariano da Silva, C. R [UNESP] (2015)
The main goal of this thesis is to study, under a historical perspective, the creation and development of the first four undergraduate courses of teachers formation in the state of Mato Grosso do Sul (Brazil). The project is part of a global project called Mapping the Math Teachers Formation in Brazil, developed by GHOEM - the Research Group Oral History and Mathematics Education. Three of these four courses were developed in different cities (Campo Grande, Três Lagoas and Corumbá) but all of them are part of the same Institution (the Federal University of Mato Grosso do Sul - UFMS), and the fourth one was created in a catholic school nowadays called Universidade Católica Dom Bosco. The written version of the study is presented in two distinct parts: in the first one, readers will find the narratives of teachers that taught in those courses in its beginning; in the other part there is the narrative of the author of the thesis and such narrative was build based on a set of written and oral documents - including the narratives presented in the first part of the thesis. The author's narrative emphasizes, at the same time, the historical elements of the process of creating and developing the undergraduate courses, and the narrative approach that characterizes the study